Concurrent Mpox and HSV-1 Proctitis in a Young Male With AIDS: A Case Report of Treatment Failure - Mikhail Sukhoroslov; Fouad Kaddour-Hocine; Muhammad Hammad Ashraf; Navya Mandalapu; Shivani Bansal; Matthew Peachey (Case Reports in Infectious Diseases, 2025)
Managing the mpox in patients with advanced HIV infection and coinfections poses significant challenges. This report discusses a young male with advanced HIV (CD4 count 28) and severe concurrent mpox and HSV-1 proctitis. Despite initial treatment with oral tecovirimat, acyclovir, and antiretrovirals, the patient’s condition worsened, requiring readmission. The patient received intravenous tecovirimat, vaccinia immune globulin, and brincidofovir. Sigmoidoscopy revealed extensive rectal and sigmoid lesions that necessitated prolonged hospitalization and pain management. This case emphasizes the complexity of treating severe coinfections in immunocompromised patients, highlighting the need for a multidisciplinary approach and consideration of alternative therapies when standard treatment fails.